Dinuclear copper(II) complexes with distant metal centers: weaker donor groups increase catecholase activity - Zerón, Paulino; Westphal, Michael; Comba, Peter (European journal of inorganic chemistry, 2017)
Two dinuclear complexes with Cu···Cu distances above 7 Å were characterized by X-ray diffraction, EPR spectroscopy, solution speciation, and cyclic voltammetry. Both complexes display EPR spectra typical of dipole-dipole-coupled dicopper(II) complexes. The two complexes presented herein are part of a series of dinuclear complexes with catecholase activity, and they exhibit the highest catalytic efficiencies of the series. This is associated with the weaker donor character of the ligands.